The relationship between lay beliefs about the world and pandemic-related beliefs, attitudes, and behaviors - Julia Marie Jankowski; Kata Sik; Veronika Job (PLoS ONE, 2025)
The Covid-19 pandemic created a strong need to understand how people can be motivated to engage in protective health behaviors (such as vaccination). Past research suggests that perceiving a health threat as serious and protective behaviors as beneficial increases people’s motivation to engage in protective behavior. However, perceptions of the seriousness of the threat and the effectiveness of protective behavior can be ambiguous in the context of a novel, global pandemic. Research on climate change suggests that people’s core understanding of the world (as either stable and unchangeable or dynamic and influenced by humans) influence whether people perceive such abstract threats to be serious and protective behaviors to be effective on a large scale. Across five online studies ( N = 1663), we investigated the correlational relationship and causal effect of these lay beliefs about the world on beliefs, attitudes, and behavioral inclinations regarding both Covid-19 and a hypothetical pandemic scenario. The results did not support a causal effect of lay beliefs about the world, but consistently showed correlational relationships. A sixth online study ( N = 410) tested a possible reversed causal effect of pandemic-related behavior inclinations being justified by shifting one’s lay beliefs about the world accordingly. However, we did not find evidence for this effect either. These results indicate that lay beliefs about the world are associated with perceptions of pandemic health threats, but their causal role is unclear.